Proximate Composition and Bacterial Quality of Fresh and Preserved Indian Major Carp Labeo rohita (Hamilton, 1822) - Hitesh U. Shingadia; Mahesh Korna; Vaibhav Prakash (Journal of Indian Fisheries Association, 2020)
Fish is an important food resource for human consumption and a major component of the aquatic ecosystem; thus forming good source of protein rich edible commodity. The aim of the present investigation was to access the changes in parameters like proximate composition and bacterial count in muscles of the Labeo rohita (Hamilton, 1822) at the culmination of preservation period of fifteen days at room temperature. In the present study, eﬀects of dry-salted, pickle-salted, brine-salted and bio-preserved salting on the production of superior quality salted dressed Rohu and their nutritive value was evaluated Under fresh conditions, the protein moisture fat ash content and salt contents were found to be 17.94±1.223%, 77.46±2.807%, 2.50±0.502%, 1.59±1.11%, and zero percent, respectively. Under preserved conditions, the protein contents were 11.54±0.11%, 22.32±2.92%, 19.26±0.292% and 17.17±2.61%; the moisture content were 45.51±1.14%, 53.91±3.06%, 67.33±0.22% and 81.8±3.02%; the fat content were 3.81±1.301%, 3.29±3.03%, 2.67±0.21% and 2.09±3.89%; the ash content were 30.32±1.03%, 26.84±3.91%, 21.99±2.35% and 11.45±1.781%; and the salt content were 17.18±2.16%, 17.94±0.34%, 16.08±4.01% and 17.53±2.78%, respectively. All these parameters were likely to show marginal variations when compared with fresh fish muscle. The bacterial quality of fish (in CFU/g) for fresh, dry-salted, pickle-salted, brine- salted, and bio- preserved salting, for SPC were 5.5x104, 4.5x104, 4.1x104, 3.9x104 and 2.7x104; for HBC were zero, 3.2x103, 3.5x103, 4.3x103 and 2.9x103, respectively. All these parameters also showed marginal variation when compared with the fresh Rohu muscle tissue. However, QCQA profile needs to be elucidated for complete safety of the preserved dressed fish.